The nutritional functions of dietary sphingomyelin and its applications in food - Yang, Fang; Chen, Guoxun (Frontiers in Nutrition, 2022)
Sphingolipids are common structural components of cell membranes and are crucial for cell functions in physiological and pathophysiological conditions. Sphingomyelin and its metabolites, such as sphingoid bases, ceramide, ceramide-1-phosphate, and sphingosine-1-phosphate, play signaling roles in the regulation of human health. The diverse structures of sphingolipids elicit various functions in cellular membranes and signal transduction, which may affect cell growth, differentiation, apoptosis, and maintain biological activities. As nutrients, dietary sphingomyelin and its metabolites have wide applications in the food and pharmaceutical industry. In this review, we summarized the distribution, classifications, structures, digestion, absorption and metabolic pathways of sphingolipids, and discussed the nutritional functioning of sphingomyelin in chronic metabolic diseases. The possible implications of dietary sphingomyelin in the modern food preparations including dairy products and infant formula, skin improvement, delivery system and oil organogels are also evaluated. The production of endogenous sphingomyelin is linked to pathological changes in obesity, diabetes, and atherosclerosis. However, dietary supplementations of sphingomyelin and its metabolites have been shown to maintain cholesterol homeostasis and lipid metabolism, and to prevent or treat these diseases. This seemly paradoxical phenomenon shows that dietary sphingomyelin and its metabolites are candidates for food additives and functional food development for the prevention and treatment of chronic metabolic diseases in humans.